Prostate-specific antigen nadir within 1 year of radiotherapy combined with hormone therapy predicts cancer-specific mortality and biochemical recurrence-free survival in prostate cancer patients - ALSAN ÇETİN, İLKNUR (My University, 2022)
Background In this study, we investigated the ability of prostate-specific antigen (PSA) 12 months after (nPSA12) external beam radiotherapy (EBRT) combined with androgen deprivation therapy (ADT) to predict biochemical recurrence-free survival (BRFS), overall survival (OS), and prostate cancer-specific mortality (PCSM) in intermediateand high-risk prostate cancer patients. Methods We retrospectively reviewed the clinical data of 338 intermediate- and high-risk prostate cancer patients treated with EBRT with ADT at our institution between 2000 and 2018. The median radiation dose was 76 Gy, the median initial PSA level was 17 ng/mL (range, 1–228 ng/mL), and the median duration of ADT was 24 months (range, 6–167 months). The median PSA level 1 months after EBRT was 0.06 ng/mL (range, 0–25.6 ng/mL). Univariate and multivariate analyses were performed. Patient survival was assessed using the Kaplan-Meier method and Cox proportional hazards regression analyses. Results The median follow-up time was 5 years (range, 1–20 years). Multivariate analysis revealed that nPSA was an independent and significant factor associated with OS, PCSM, and BRFS (P = 0.008, P = 0.001, P = 0.04). Furthermore, the time to nPSA12 was an independent predictor of PCSM and BRFS (P = 0.042, P = 0.021). Pelvic irradiation was also significantly associated with worse OS and PCSM (P = 0.004, P = 0.01). Additionally, age (≤ 70 or > 70 years) and hormone therapy duration (6 months, 1–3 years, or > 3 years) were significantly associated with OS and PCSM, respectively (P = 0.004, P = 0.02). For high risk, nPSA and nPSA12 were an independent predictor for BRFS. (P = 0.021, P = 0.029) Conclusion The nPSA12 level of > 0.06 ng/mL may independently predict worse PCSM and BRFS in intermediateand high-risk prostate cancer patients undergoing EBRT and ADT. Additionally, for high risk, nPSA > 0.06 ng/mL and nPSA12 > 0.06 ng/mL may independently predict worse BRFS.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)